2016
DOI: 10.5152/balkanmedj.2016.16566
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Glu298Asp Polymorphism and Endothelial Dysfunction in Patients with and without End-stage Renal Disease

Abstract: Background: Chronic kidney diseases are known to influence nitric oxide metabolites (NOx) and asymmetric dimethylarginine (ADMA), though the exact mechanism is still poorly understood. Aims: The purpose of the present study was to examine eNOS Glu298Asp gene polymorphism, plasma NOx and ADMA concentration in subjects with and without End-stage Renal Disease. Study Design: Case-control study. Methods: In this study, genotype distributions of Glu298Asp in exon 7 of the eNOS gene polymorphisms in 130 hemodialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…We aimed to evaluate the association of eNOS Glu298Asp and ACE I/D gene polymorphism with GDM in Iranian GDM women. Several studies have been conducted to investigate the relationship between eNOS gene polymorphism and multiple diseases; Ilhan N et al did not observe any association between the Glu298Asp polymorphism in the eNOS gene and end-stage Renal Diseases [17]. Martinelli NC et al showed that the -786C/4b/Asp298 eNOS haplotype had a significant impact on heart failure susceptibility and prognosis, particularly in African-Brazilian patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to evaluate the association of eNOS Glu298Asp and ACE I/D gene polymorphism with GDM in Iranian GDM women. Several studies have been conducted to investigate the relationship between eNOS gene polymorphism and multiple diseases; Ilhan N et al did not observe any association between the Glu298Asp polymorphism in the eNOS gene and end-stage Renal Diseases [17]. Martinelli NC et al showed that the -786C/4b/Asp298 eNOS haplotype had a significant impact on heart failure susceptibility and prognosis, particularly in African-Brazilian patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above data, Ilhan N. et al (2016) [19] studied the Glu298Asp eNOS gene polymorphism and endothelial dysfunction in the patients with and without end-stage RF (ESRF) and did not reveal any interdependence between the Glu298Asp eNOS gene polymorphism and ESRF in the group of patients under examination. In the work of Marson B.P.…”
Section: Fig 2 the State Of The Initial Renal Filtration Function Imentioning
confidence: 89%